2023
DOI: 10.1002/pri.2002
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming in the treatment of gait, balance, and quality of life in Parkinson's disease: Overview of systematic reviews

Abstract: Introduction:Postural instability and gait impairments are common in people with PD, both of which have a negative effect on their quality of life. Systematic reviews have demonstrated benefits of using exergaming in enhancing these outcomes.However, there is no consensus over whether exergaming therapy is better than conventional physical therapy for enhancing gait, balance, and quality of life. Objectives: The aim of this overview is to systematically synthesize and evaluate the available evidence found in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…showed that there is potential for PD rehabilitation with exercise gaming treatment [15]. A study by Maranesi et al concluded that with its integration of cognitive and physical activities inside a virtual, enhanced, or interactive gaming environment, exergaming-based technological rehabilitation might be more innovative than the traditional approach [16].…”
Section: Discussionmentioning
confidence: 99%
“…showed that there is potential for PD rehabilitation with exercise gaming treatment [15]. A study by Maranesi et al concluded that with its integration of cognitive and physical activities inside a virtual, enhanced, or interactive gaming environment, exergaming-based technological rehabilitation might be more innovative than the traditional approach [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of keyword burst and cluster analysis motor function in people with PD has received increasing attention from researchers in the past decades. This reason can be the freezing of gait is one of the common motor symptoms in patients with PD and is a major risk factor for falls, which greatly reduces mobility and quality of life ( Giladi and Nieuwboer, 2008 ; Nutt et al, 2011 ; Rocha et al, 2023 ). Recent studies suggested that TMS has a certain improvement effect on some indicators of gait in people with PD, and this effect is not maintained in the long term, but only in the short term ( Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%